Performance Analysis of Assistant Secretariat Expenditure Treasurer at the Plantation Office of North Sumatra Province - Dinda Savira Viantika; Annio Indah Lestari Nasution (Penerbit Jurnal Indonesia, 2022)
Manpower is one of the most important assets in an agency or organization where it takes workers who understand responsibilities and have good performance, this will be obtained if the workforce has good job satisfaction as well. The purpose of this study was to analyze the work performance of the assistant treasurer of expenses and the method used in this study was descriptive qualitative with observations and interviews. As for the results of the study it was found that the assistant treasurer's work performance decreased due to a lack of personnel in the treasury which caused less coordination of work responsibilities.